Peran Dinas Perindustrian dan Tenaga Kerja dalam Acara Job Fair Next Leader Expo untuk Menekan Angka Pengangguran di Kota Surabaya - Fasich Rahman Hendyarta Permana; Tukiman (MES Management Journal, 2024)
Based on the 1945 Constitution Article 27 Paragraph 2 which reads "Every citizen has the right to work and a decent living for humanity." have a decent job in order to earn enough to survive and compete with other workers. This research focuses on employment problems, especially in the unemployment sector, with the massive free work exchange program being held by the Department of Industry and Manpower which will certainly be useful for reducing the unemployment rate. So the aim of this research is to find out the extent to which the Department of Industry and Manpower plays a role as a stabilizer, innovator, modernizer and pioneer in reducing unemployment in the city of Surabaya. Data collection techniques use interviews, observation and documentation. The results of this research can be said that the role of the Department of Industry and Manpower has gone well, by collaborating with 70 companies and providing 1211 job vacancies at this free job fair which will really help the employment sector in reducing unemployment in the city of Surabaya.